The Influence of Financial Literacy, Financial Inclusion and Innovation on the Financial Performance of MSMEs in the Marble Processing Industry Sector - Satwara, Elindya Noviantika; Istanti, Lulu Nurul (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The main problems faced by MSMEs in the Marble Processing Industry Sector in Campurdarat District are limited business capital, low level of financial knowledge and limited innovation. To maximize financial performance and sustainability of MSMEs, quality and high-value internal resources are needed. This study aims to find out and learn how the influence of financial literacy, financial inclusion and innovation as internal business resources on the financial performance of Marble Stone Industry MSMEs in Campurdarat District, Tulungagung Regency. The research was conducted using a quantitative method and involved as many as 75 samples obtained by the accidental purposive sampling method. The data processing of the questionnaire results was carried out by multiple linear regression analysis through SPSS. The results of the study show that financial literacy and innovation partially have a positive and significant effect on financial performance, financial inclusion has no significant effect on the financial performance of MSMEs, and simultaneously financial literacy, financial inclusion and innovation has a significant positive effect on the financial performance of MSMEs